Continuous on-sun solar thermochemical hydrogen production via an isothermal redox cycle. (1st September 2019) - Hoskins, Amanda L.; Millican, Samantha L.; Czernik, Caitlin E.; Alshankiti, Ibraheam; Netter, Judy C.; Wendelin, Timothy J.; Musgrave, Charles B.; Weimer, Alan W.
Graphical abstract: Highlights: Continuous, isothermal on-sun solar thermochemical hydrogen production demonstrated. Hercynite particles generated 5.3 L of H2 in 8 h on-sun (597 µmol H2 /g). Hercynite particles were stable over multiple days on on-sun redox testing. Important factors for commercial scaling identified with techno economic analysis. Economic analysis showed strong dependence on use of robust, inexpensive materials. Abstract: Solar thermochemical hydrogen production from water is a path towards a carbon-free sustainable hydrogen economy. Here, isothermal on-sun hydrogen production is demonstrated using active iron aluminate (hercynite) particles contained in dual fluidized bed reactors. The two fluidized beds were held in a single cavity solar receiver that was heated with a 10 kW high flux solar furnace. During 8 h of on-sun testing, 5.3 L of H2 were generated with an average productivity of 597 µmol H2 /g using an intermittent process with optimized redox cycle times. Redox cycling was performed isothermally and continuously with equivalent oxidation and reduction times producing 547 µmol H2 /g over two cycles. These results show excellent agreement with the H2 production measured in an 800X scaled-down electrically heated laboratory stagnation flow reactor and surpass on-sun H2 production of current benchmark materials. The effect of environmental variability on the incident solar radiation and hydrogen production is evaluated during on-sun testing. Finally, a discussion of the important factors for scalability of the process to commercial applications is provided, highlighting the importance of robust containment and active materials. This work links current materials research and development with commercial implementation in an on-sun process and demonstrates the viability of solar thermochemical hydrogen production that leverages continuous isothermal redox cycling.